Healthy lifestyle interventions in general practice: Part 15: Lifestyle and lower back pain - M.P. Schwellnus; D.N. Patel; C. Nossel; S. Whitesman; E.W. Derman (South African Family Practice)
Lower back pain (LBP) is one of the most common medical problems in the adult population. LBP can be defined as pain, muscle tension or stiffness that is localised below the costal margin (inferior rib cage) and above the inferior gluteal folds and that can present either with or without leg pain (sciatica), and it can be classified as “specific” or “non-specific”. LBP has a high lifetime prevalence and is associated with a substantial direct and indirect cost to the individual and society. In this review, the focus is on the identification of lifestyle risk factors and interventions that are associated with mainly nonspecific chronic LBP. In addition to pharmacotherapy, the best treatment approach is exercise therapy (including physical reconditioning), psychosocial and behavioural intervention and therapeutic education. Other lifestyle changes include nutritional intervention and smoking cessation.